2016
DOI: 10.3390/ijms17060935
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of 5-Methoxytryptamine-α-lipoic Acid on Ionizing Radiation-Induced Hematopoietic Injury

Abstract: Antioxidants are prospective radioprotectors because of their ability to scavenge radiation-induced reactive oxygen species (ROS). The hematopoietic system is widely studied in radiation research because of its high radiosensitivity. In the present study, we describe the beneficial effects of 5-methoxytryptamine-α-lipoic acid (MLA), which was synthesized from melatonin and α-lipoic acid, against radiation-induced hematopoietic injury. MLA administration significantly enhanced the survival rate of mice after 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…Radiation produces DNA damage directly through reactive oxygen species 33 , and destroys the expression of proteins in cells 34 , activating p53 4 , 33 , 35 , 36 . In addition, DNA injury induced by IR was determined by γH2AX phosphorylation, and this was used as an indicator for quantifying DNA double-strand breaks 37 . Recent studies suggest that p53 in intestinal epithelial cells principally controls radiation-induced GI toxicity in mice, independently of apoptosis 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiation produces DNA damage directly through reactive oxygen species 33 , and destroys the expression of proteins in cells 34 , activating p53 4 , 33 , 35 , 36 . In addition, DNA injury induced by IR was determined by γH2AX phosphorylation, and this was used as an indicator for quantifying DNA double-strand breaks 37 . Recent studies suggest that p53 in intestinal epithelial cells principally controls radiation-induced GI toxicity in mice, independently of apoptosis 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy for cancer treatment increased the risk of myelosuppression. Irradiation may cause dysfunction in multiple cells and various tissues, especially hematopoietic failure and immune impairment (Kim et al, ; Li et al, ). Bone marrow is the most important hematopoietic organ and highly susceptible to irradiation injury, because it keeps a high rate of cell proliferation and composes different developmental stages of hematopoietic cells (Bentzen, ).…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, development of an effective method and drug to mitigate the radiation-induced intestinal injuries needs to be explored. Many studies have reported that Chinese herbal medicines or extracts and other drugs may be able to reduce TBI-induced injuries in the brain, oesophagus and haematopoietic system of irradiated animals, [14][15][16][17][18] but the study of protective drugs in IR-induced intestinal injuries still needs to be improved. [19][20][21] In the present study, we observed that the new compound XH-105 had protective effects on radiation-induced intestinal injuries.…”
Section: Discussionmentioning
confidence: 99%